Reimagining Journalism: Exploring the AI Revolution - A Thorough Analysis of Potential Advantages and Challenges - Moehammad Iqbal Sultan; Abu Jafar Md. Shafiul Alam Bhuiyan; Andi Subhan Amir (Komunikator, 2024)
The integration of Artificial Intelligence (AI) into journalism has caused a significant shift in the industry. AI-powered tools are now a part of the journalistic workflow, transforming how news is collected, reported, and shared. These tools can assist with fact-checking, research, and content generation. This technological advancement has the potential to revolutionize how we interact with news in the digital age. In this article, we explore the relationship between AI and journalism, examining its advantages and challenges. Through a comprehensive analysis of academic literature and interviews with experts in journalism and AI, this article embarks on a journey of discovery. It concludes that a balanced and ethical approach is crucial to the integration of AI in journalism. The article emphasizes the importance of ethical guidelines to govern the use of AI in newsrooms, with a focus on transparency, accountability, and eliminating bias. As AI-infused journalism continues to evolve, it is the responsibility of journalists to ensure that this technological marvel enhances human capabilities and does not undermine the fundamental principles of journalism.